Relocation method of microseismic source in deep mines - Huang, L.; Li, X.; Dong, Li; Zhang, C.; Liu, D. (Nonferrous Metals Society of China, 2016)
A new method, named relocation, was proposed to reduce the impact of sensor errors systematically, especially when available data of sensors are abundant. The procedure includes evaluating the reliability of every sensors datum, processing the initial location by the credible data, and selecting a set of equations with optimal noise tolerance according to the relative relationship between the initial location and sensors location, then calculating the final location by k-mean voting. The results obtained in this research include comparing traditional location method with the presented method in both simulation and field experiment. In the field experiment, the location error of relocation method reduced 41.8% compared with traditional location method. The results suggested that relocation method can improve the fault-tolerant performance significantly.